Where are they now?- Report on a 22 year longitudinal study of elite distance runners - Trappe, S. W.; Costill, D. L.; Vukovich, M. D.; Jones, J.; Melham, T.
This study substantially supports the findings of several other shorter term longitudinal studies of masters athletes as well as several good cross sectional studies. The main point is of course, a continued high level of training can significantly reduce the magnitude of VO2 decline that inevitably occurs with aging. Previously, a 9-10% decline in maximal oxygen consumption/decade has been suggested from studies of untrained healthy men. As suggested by other studies, the results above suggest that the rate of decline is halved (5% /decade and in some cases even less) in athletes who maintain a very high level of training volume and intensity. As we have discussed before. Continued training can maintain stroke volume at high levels, as well as skeletal muscle endurance capacity. Maximal heart rate decline with age, on the other hand, is not altered by activity level.